1997
DOI: 10.1136/jnnp.63.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological, psychiatric, and cerebral perfusion correlates of leukoaraiosis in Alzheimer's disease

Abstract: Objective-To examine neurological, neuropsychological, psychiatric, and cerebral perfusion correlates of leukoaraiosis in Alzheimer's disease. Methods-A consecutive series of patients with probable Alzheimer's disease was assessed with a comprehensive neuropsychological battery, a structured psychiatric evaluation, the unified Parkinson's disease rating scale, MRI, and single photon emission computed tomography with technetium 99m hexamethylpropyleneamine oxime (HMPAO) and regional cerebral perfusion measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
75
3
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 38 publications
(27 reference statements)
7
75
3
2
Order By: Relevance
“…72 Positive associations between WM changes and psychiatric symptoms have been reported in subjects without dementia. 73,74 Although previous studies have failed to find a relationship between WM changes and neurobehavioral signs in patients with dementia, 14,21,28,30 the present study clearly demonstrated that WM changes were involved in the development of aberrant motor behaviors. Aberrant motor behaviors, including wandering, pacing, and rummaging, belong to repetitive and excessive behaviors, which are likely to be caused by frontal lobe dysfunction.…”
Section: Discussionmentioning
confidence: 52%
“…72 Positive associations between WM changes and psychiatric symptoms have been reported in subjects without dementia. 73,74 Although previous studies have failed to find a relationship between WM changes and neurobehavioral signs in patients with dementia, 14,21,28,30 the present study clearly demonstrated that WM changes were involved in the development of aberrant motor behaviors. Aberrant motor behaviors, including wandering, pacing, and rummaging, belong to repetitive and excessive behaviors, which are likely to be caused by frontal lobe dysfunction.…”
Section: Discussionmentioning
confidence: 52%
“…3 Because WMH most probably represent ischemic small vessel disease, 1,4 we hypothesized that subjects with diffuse confluent WMH should have lower cerebral blood flow (CBF) measurements than subjects with punctiform or beginning confluent WMH. In fact, single-photon emission CT, positron-emission tomography, and dynamic susceptibility contrast perfusion-weighted MR imaging studies have shown that diffuse confluent WMH are associated with reduced cerebral perfusion, [5][6][7] but most of them did not yield quantification of CBF. To our knowledge, no previous study has shown a relation between different grades of WMH and CBF measurements by means of ASL.…”
mentioning
confidence: 99%
“…Some studies have found relationships between various BPSD and subcortical lesions (foremost in the white matter) in AD. These include positive associations with anxiety [6], aberrant motor behavior [6,7], apathy [8] and depression [9] as well as a trend for delusions [6]. However, other studies have failed to confirm these associations [10,11,12,13].…”
Section: Introductionmentioning
confidence: 95%
“…One way of examining its independent impact on BPSD is to adjust for atrophy (both global and temporal) and cognitive ability, which are closely related to AD pathology and disease severity [23,24,25]. Unfortunately, many previous studies did not adjust for atrophy [6,8,9]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation